ASSESSMENT OF THE IMPACT OF SOME SOCIO-ECONOMIC INDICATORS ON INDUSTRIAL DEVELOPMENT IN SURKHANDARYA REGION ON THE BASIS OF REGRESSION ANALYSIS (Conference Zone, 2022)
In this paper evaluated the effect of some socio-economic indicators on the development of industry sector in Surkhandarya region. For this, used coefficients of elasticity determined on the basis of regression analysis. Based on the results obtained, prospective directions for industrial development in the region have been identified